2020
DOI: 10.1055/a-1266-6674
|View full text |Cite
|
Sign up to set email alerts
|

Achiote (Bixa orellana) Lipophilic Extract, Bixin, and δ-tocotrienol Effects on Lifespan and Stress Resistance in Caenorhabditis elegans

Abstract: The onset of many degenerative diseases related to aging has been associated with a decrease in the activity of antistress systems, and pharmacological interventions increasing stress resistance could be effective to prevent the development of such diseases. Achiote is a valuable source of carotenoid and tocotrienols, which have antioxidant activity. In this work, we explore the capacity of an achiote seed extract and its main compounds to modulate the lifespan and antistress responses on Caenorhabditis elegan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
(73 reference statements)
0
0
1
Order By: Relevance
“…[47] showed that C. elegans subjected to oxidative stress with hydrogen peroxide had decreased lifespan and increased lipofuscin accumulation. On the other hand, animals treated with a tocotrienols-rich fraction had restored lifespan and reduced lipofuscin [48] reported that the lipophilic extract of B. orellana increased the median and maximum lifespan by 35% and 27%, increasing oxidative and thermal stress without affecting the fertility (which is different from what was observed here). According to the authors, the effect depended on the insulin/insulin growth factor-1 pathway.…”
Section: Discussioncontrasting
confidence: 99%
“…[47] showed that C. elegans subjected to oxidative stress with hydrogen peroxide had decreased lifespan and increased lipofuscin accumulation. On the other hand, animals treated with a tocotrienols-rich fraction had restored lifespan and reduced lipofuscin [48] reported that the lipophilic extract of B. orellana increased the median and maximum lifespan by 35% and 27%, increasing oxidative and thermal stress without affecting the fertility (which is different from what was observed here). According to the authors, the effect depended on the insulin/insulin growth factor-1 pathway.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies in the literature report that some plant secondary metabolites can aid in longevity by acting on molecular pathways that modulate stress resistance and metabolic efficiency. In line with the results observed here, some phytochemical compounds present in Terasen ® have been reported to increase the lifespan and stress resilience in C. elegans and other organism, including anthocyanins [26][27][28][29][30][31][32], quercetin [33,34], polyphenols [28,35], carotenoids [36,37], and tocotrienols [38,39].…”
Section: Discussionsupporting
confidence: 90%